Efficiency of two sewage treatment systems (activated sludge and natural lagoons) for helminth egg removal in Morocco - Sana Chaoua; Samia Boussaa; Ahmed Khadra; Ali Boumezzough (Elsevier, 2018)
Morocco is a country known for its vulnerability of water resources because of its arid and semi-arid climate. Thus, recycled wastewater has been suggested for agricultural activities, but contamination of these wastewaters is a major concern.The current study aims to determine the occurrence of helminth eggs in urban wastewater and to evaluate the removal of these pathogens by two sewage treatment systems: activated sludge and natural lagoons. The samples of wastewater and sludge were collected from two wastewater treatment plants (WWTP) located in Marrakech and Chichaoua, Morocco.Parasitological identification, according to the Bailenger technique, showed the presence of Nematodes and Cestodes, which are pathogenic to humans and animals and are responsible for helminthiasis. The wastewater and sewage sludge samples from Marrakech carried Ascaris lumbricoïdes, Ancylostoma duodenale, Trichuris trichiura, Capillaria spp., Taenia spp. and Hymenolepis spp., while the samples from Chichaoua carried Ascaris lumbricoïdes, Ancylostoma duodenale, Trichuris trichiura and Capillaria spp.The overall removal efficiency of eggs in the treatment plants ranged from 100% in the WWTP of Marrakech using activate sludge to 94.97% in the WWTP of Chichaoua using natural lagoons. These results were discussed according to health risk and the cost-effectiveness of both wastewater treatment techniques. Keywords: Infectious agents, Activated sludge, Natural lagoons, Helminth eggs, Morocco